Question Number 207248 by hardmath last updated on 10/May/24 | ||
![]() | ||
$$\mathrm{If}\:\:\:\mathrm{f}\left(\mathrm{x}\right)\:=\:\mathrm{3}^{\boldsymbol{\mathrm{x}}+\mathrm{1}} \\ $$$$\mathrm{Find}\:\:\:\frac{\mathrm{f}\left(\mathrm{2x}\:+\:\mathrm{1}\right)}{\mathrm{f}\left(\mathrm{x}\:+\:\mathrm{2}\right)}\:\:=\:\:? \\ $$ | ||
Answered by A5T last updated on 10/May/24 | ||
![]() | ||
$$?=\frac{\mathrm{3}^{\mathrm{2}{x}+\mathrm{2}} }{\mathrm{3}^{{x}+\mathrm{3}} }=\mathrm{3}^{{x}−\mathrm{1}} \\ $$ | ||